PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN PENDIDIKAN PANCASILA YANG BERDIFERENSIASI PADA SISWA KELAS V SEKOLAH DASAR - Vita Kurniawati; Amalia Sapriati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the application of a differentiated Problem Based Learning (PBL) learning model in learning Pancasila Education with the material “Becoming a Great Child by Applying Norms” in grade V elementary school. This research uses a qualitative method with a case study design. The research subjects were 13 fifth grade students of SD Negeri 01 Buran. Data were collected through observation, interviews, and documentation, then analyzed using a qualitative descriptive approach. The results showed that the implementation of differentiated PBL effectively increased students' active participation, critical thinking skills, and their understanding of the application of norms in daily life. Differentiation is applied through variations in content, process, and product that are tailored to students' learning needs. In addition, the PBL model used provides meaningful learning experiences involving real problem solving. This study concludes that differentiated PBL is effective in increasing student engagement as well as concept understanding, and provides positive implications for the development of 21st century skills. This study recommends that teachers adopt PBL methods with differentiation in mind to create more inclusive learning that meets students' needs.